2015
DOI: 10.1155/2015/575376
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure Studies and Photocatalytic Properties of Cubic Bi1.5ZnNb1.5O7

Abstract: The photocatalytic ability of cubic Bi 1.5 ZnNb 1.5 O 7 (BZN) pyrochlore for the decolorization of an acid orange 7 (AO7) azo dye in aqueous solution under ultraviolet (UV) irradiation has been investigated for the first time. BZN catalyst powders prepared using low temperature sol-gel and higher temperature solid-state methods have been evaluated and their reaction rates have been compared. The experimental band gap energy has been estimated from the optical absorption edge and has been used as reference for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…27 Our recent investigations on the electronic band structures of cubic-BZN and cubic-BZT have shown that the use of the (widely accepted) CIFs as inputs for Density Functional Theory (DFT) calculations, result in complete absence of electronic band gaps when using the Full Plane Wave Functions of the Cambridge Serial Total Energy Package (CASTEP) of Materials Studio. 28,29 These results contradict the reported experimental observations of optical band gaps of 3.0-3.2 eV. 30,31 A band gap is obtained for fractional occupancy of cations in BZT using the Linear Muffin Tin Potential.…”
Section: Introductionmentioning
confidence: 72%
See 4 more Smart Citations
“…27 Our recent investigations on the electronic band structures of cubic-BZN and cubic-BZT have shown that the use of the (widely accepted) CIFs as inputs for Density Functional Theory (DFT) calculations, result in complete absence of electronic band gaps when using the Full Plane Wave Functions of the Cambridge Serial Total Energy Package (CASTEP) of Materials Studio. 28,29 These results contradict the reported experimental observations of optical band gaps of 3.0-3.2 eV. 30,31 A band gap is obtained for fractional occupancy of cations in BZT using the Linear Muffin Tin Potential.…”
Section: Introductionmentioning
confidence: 72%
“…28,29 The DFT calculations on BZN and BZT also predict small modications from the cubic structure, when complete substitution order is assumed, which appears favoured as attested by the signicantly more negative enthalpy of formation. 28,29 However, such favourably calculated modied structures could not be clearly detected by standard X-ray diffraction (XRD) or transmission electron microscopy (TEM) characterizations. An overall cubic structure, predicted by the DFT calculation, could be reconciled by assuming partial order, with order just on the B-sites, while the A-sites remained randomly substituted.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations